COMMUNIO-KOINONIA MENURUT VISI PAROKI KATEDRAL KRISTUS RAJA DALAM PERTEMUAN AKSI PUASA PEMBANGUNAN - Dhimas Martin Yuniar (Jurnal Teologi (Journal of Theology), 2013)
Diocese of Purwokerto idealizes a community of Gods Kingdom Church, which by then becomes a together movement of the Catholics in Diocese of Purwokerto. Each parish, including Parish Cathedral Kristus Raja of Purwokerto, makes a vision which is appropriate with the need and situation of the Catholics in this parish. The event of Aksi Puasa Pembangunan, becomes a method that is really suitable with the efforts of this Church in presenting a community which is communious internally and externally as well. In this research, the intention of APP, is not fully caught and comprehended by the Catholic people of Cathedral Kristus Raja of Purwokerto. Therefore APP meeting have not really helped the Cathedral to build its communitys identity. To make it more effective and efficient in presenting the ideal community, Cathedral Kristus Raja of Purwokerto needs to make some pastoral steps. It is hoped that APP can become a program to build a community which is holy, autonomic, mature, dynamic, growing in true brotherhood and becoming the light and salt of world.